KEBUGARAN JASMANI MAHASISWA PENDIDIKAN OLAHRAGA FKIP UNIVERSITAS BINA DARMA - HARDIYONO, BAYU (Publikasi Penelitian Terapan dan Kebijakan, 2011)
The need for physical capabilities for each individual is different, this difference is usually influenced by the type of work each individual, for post secondary students, the physical ability is important to support learning, manage classes, or doing other activities, that is why each student is expected to arrival goos to have the ability to command assistance-related activities in their learning. An individual has the physical ability is good if he or she meets either flat according to certain parameters, one parameter for standardization Asia comitte physical ability test (A, C, S, P, F, T) for university students which includes seven kinds of testing. The results indicate that the status of students' abilities in sports education Universita Bina Darma S1 is the ability (98.12%) and the only physical ability (1.88%). With detailed, their physical abilities can be categorized: very good (26.42%), good (45.28%), moderate (26.42%) and low (1.82%). This time desdription is categorized by gender, which attended a category will be like: very good male students (26.19%), good (27.27%), good (31.82%), moderate (36.36%) and low (4:55%). Most of the weights used to index (83.02%) and only a handful of students are not normal (16.98%). in more detail, a lot of body fat index is (6.60%), normal (83.02%), lack of nutrition I (8.50%), lack of nutritional science ii (0.94%) and lack of nutrition (0.66%). basing on gender, body mass index is a male student (3.57%), normal (86.90%), lack of nutrition I (9,57%). None of them in the category of lack ofnutrition ii and iii, whereas body mass index is a fat female students (18:18%), normal (68.17%), lack of nutrition I (4,55%), lack of nutritional science ii (4,55% ),and lack of nutrition iii (4,55%).